Financial performance: The impact of age and background of retired military officers on oil, gas, and coal companies - Chudri, Intan Rizkia; Fadilla, Fitrah; M.J, Ermad (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to investigate the impact of the age and background of retired military officers in management roles on the financial performance of companies. Methodology/Approach: The research was conducted across 22 companies operating in the Oil, Gas, and Coal sub-sector, selected based on specific criteria. The study utilized a quantitative approach, employing panel data regression analysis to assess the relationship between the independent variables (age and background of retired military officers) and the dependent variable (financial performance) over the period from 2021 to 2023. Results: The results of this study found that management age has a significant positive effect on financial performance, and military background has a significant positive effect on financial performance. Conclusions: The research concludes that the age and background of retired military officers play a critical role in shaping the financial performance of companies, particularly within the Oil, Gas, and Coal sectors. Understanding this relationship can provide valuable insights for organizations in selecting management personnel. Limitations: A limitation of this study is its focus on a specific sector, which may restrict the generalizability of the findings to other industries or contexts. Contribution: This study contributes to the fields of management and organizational behavior by highlighting the significance of leadership backgrounds in influencing financial performance. The insights gained can assist companies in making informed decisions regarding management recruitment and development strategies.